Catholic social teachings : an analytical study on Pope John Paul II's encyclical "Sollicitudo Rei Socialis" - Sayadat, Mohammad Nazmus (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University malaysia, 2011)
The present research examines the contribution of Pope John Paul II (1920-2005) in the development of Catholic social teachings through his encyclical ―Sollicitudo rei socialis‖. It starts with an overview on the present research work including objectives, questions, scope and methodology as well as the literature review. Chapter Two provides an introductory analysis of Catholicism with its theology and doctrines in social teachings. It also presents the basic features of Catholicism with the Church's mission, nature and organizational chart. Chapter Three demonstrates the understanding of Catholic social teachings by studying the encyclicals and the major themes of Pope Paul VI. Chapter Four examines and analyzes the teachings of Pope John Paul II through his encyclical ―Sollicitudo rei socialis‖. It also discusses his life and concludes with the major themes of Catholic social teachings of Pope John Paul II. Chapter Five is the findings and conclusion of the present research. The methodology employed for the study was documentary analysis, which used a combination of library research and analysis based on the original texts and materials. Finally, this research concludes with Pope John Paul II's contributions on the subject of Catholic social teachings by analyzing his encyclical ―Sollicitudo rei socialis‖. Since his works play a major role in Christianization, it is hoped that this study will help Muslims to understand the process of Christianization better and facilitate them to resist the Catholic onslaughts.